Dampak Alih Usaha Pertanian terhadap Pendapatan Pemilik Lahan di Desa Banua Binjai Kecamatan Pandawan Kabupaten Hulu Sungai Tengah - Khairunnisa; Lina Suherty (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This study aims to explain the agricultural business's impact on the land owner'ssocio-economic conditions regarding livelihood structure and ownership of agriculturalland. A factor affecting land-use change is the lack of workforce to work on or manageagricultural land in Banua Binjai Village.Landowner income before over agricultural business and after over agriculturalbusiness changes in the form of an increase. Gain occurs to people in Banua Binjaivillage over the farming business and is influenced by several factors: lack of labor towork on the land, the family's economic pressure, and the desire to open a new business.Based on paired t-test results, it is known that the t-count of -6.435 with a significancevalue of 0,000 (p <α). The test results can be concluded that accepting Ha and rejectingHo means that there is a difference in the income of landowners in Banua Binjai Villagebetween before and after land conversion.